1995
DOI: 10.1002/mrd.1080400308
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis and pronucleus development in pig zygotes obtained in vivo: An autoradiographic and ultrastructural study

Abstract: Porcine zygotes flushed from oviducts 48, 52, 56, 60, or 64 hr after hCG were incubated 30 min in 3H-thymidine, transferred to nonradioactive medium for 2 hr, and incubated for 30 min with 14C-thymidine. After this procedure, ova were prepared (i.e., at 51, 55, 59, 63, or 67 hr after hCG) for autoradiography and ultrastructural observations, respectively. The first autoradiographic labelling, i.e., DNA synthesis, was observed at 56-56.5 hr after hCG, while the latest labelling was seen at 60-60.5 hr. At 51 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…It has been proposed that human nuclear precursor bodies are formed by the aggregation of small dense bodies, which arise in association with condensed chromatin (Tesarik & Kopecny, 1989). In the present study we found intranuclear granules of varying size and shape as early as the pronuclear stage, similar to those observed in the pronuclei of porcine zygotes in vivo (Laurincik et al, 1995). In the present study we found intranuclear granules of varying size and shape as early as the pronuclear stage, similar to those observed in the pronuclei of porcine zygotes in vivo (Laurincik et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It has been proposed that human nuclear precursor bodies are formed by the aggregation of small dense bodies, which arise in association with condensed chromatin (Tesarik & Kopecny, 1989). In the present study we found intranuclear granules of varying size and shape as early as the pronuclear stage, similar to those observed in the pronuclei of porcine zygotes in vivo (Laurincik et al, 1995). In the present study we found intranuclear granules of varying size and shape as early as the pronuclear stage, similar to those observed in the pronuclei of porcine zygotes in vivo (Laurincik et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…As observed for fertilisation with isogenic species sperm (Laurincik et al, 1995), characteristic 'undulation' of the nuclear envelope is seen in porcine oocytes following murine sperm injection. This structural change may be required for specialised nucleocytoplasmic transport.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Also, cryopreservation alters DNA synthesis in different cell types, such as embryonic inner cell mass cells and fetal pancreatic cells [58,59]. In porcine zygotes, it has been suggested that DNA replication starts approximately 6 h after sperm penetration [60] and lasts for 4.5-7.5 h [61]. Although sperm and oocytes are coincubated for 3 h in our IVF system, the sperm penetration rate peaks about 4 h after insemination, probably due to penetration of spermatozoa that are in the zona pellucida or perivitelline space at 3 h after IVF (Kikuchi et al, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%